Chemical composition and sources of organic aerosol on the Adriatic coast in Croatia. (January 2022) - Casotto, R.; Cvitešić Kušan, A.; Bhattu, D.; Cui, T.; Manousakas, M.I.; Frka, S.; Kroflič, A.; Grgić, I.; Ciglenečki, I.; Baltensperger, U.; Slowik, J.G.; Daellenbach, K.R.; et al.
Abstract: Air pollution studies are still scarce in some areas in Europe like around the Adriatic Sea. Source apportionment of the fine particulate (PM2.5 ) organic aerosol (OA) was conducted near Rogoznica, a small touristic settlement on the Eastern Adriatic coast of Croatia, near Lake Rogoznica (43.53° N, 15.95° E). Filter-based offline analyses of PM by a high resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) and an extractive electrospray ionization time-of-flight mass spectrometer (EESI-TOF) were used to apportion OA to its sources. We quantified the contributions of fresh biomass burning OA (BBOA) and three oxygenated OA (OOA), denoted as background OOA (bkgOOA), summer OOA (SOOA), and sulfur-containing OOA (SC-OOA). The bkgOOA component correlates with anthropogenically influenced secondary inorganic aerosol constituents (e.g. sulfate) and dominates OA both during the warm and cold seasons (44%). It exhibits characteristics of regional SOA and there are indications that during the warm season SOA from wildfires could be a substantial contributor. EESI-TOF measurements of the levoglucosan related ion showed a high correlation with the BBOA factor. Secondary OA has a similar molecular composition during the cold and warm seasons – in line with the large contribution of bkgOOA throughout the investigated seasons. SOOA comprises 19% of total OA and increases exponentially with the local temperature, consistent with SOA production by oxidation of biogenic emissions. In addition to biogenic precursors, other precursors (alkanes and aromatic) may contribute to the OOA enhancement during the warm season. SC-OOA is a minor contributor to OA (6%) and is most likely linked to emissions from a close-by marine lake. Highlights: New error estimation for offline ToF-AMS. Estimation of WSOA through labelled ammonium nitrate. Source apportionment of WSOA and recovery to OA. Seasonal analysis with EESI-TOF measured compounds.